Temporal complexity of network resource access manager different implementations - Самойленко, Денис Миколайович (Ukrainian Information Security Research Journal, 2017)
To create a complex data protection system for network information resource in accordance with the regulatory requirements it is necessary to implement the concept of Access Manager as a single transition point of all requests. There are several different approaches to implementation of Access Manager with different reliability as a security parameter. The popular opinion is that the highest security quality Access Manager is also the slowest one. It impairs the other security quality - "availability". Fundamental researches of balance between reliability and availability for Access Managers were not carried out previously. There were implemented four versions of Access Manager for the Apache server and PHP programming language; experimental determination of Access Managers time complexity was performed with linear regression using. It is shown that differences in the time complexity does not exceed 5%, allowing you prefer the most reliable option without compromising availability. Additionally demonstrated better efficiency of language PHP 7 compared to PHP 5 in the implementation of client-server interaction. The use of the results could improve the quality of network security information resources.